Stability analysis for periodic solutions of fuzzy shunting inhibitory CNNs with delays - Kashkynbayev, Ardak; Cao, Jinde; Damiyev, Zhaksybek (SpringerOpen, 2019)
We consider fuzzy shunting inhibitory cellular neural networks (FSICNNs) with time-varying coefficients and constant delays. By virtue of continuation theorem of coincidence degree theory and Cauchy–Schwartz inequality, we prove the existence of periodic solutions for FSICNNs. Furthermore, by employing a suitable Lyapunov functional we establish sufficient criteria which ensure global exponential stability of the periodic solutions. Numerical simulations that support the theoretical discussions are depicted.
https://advancesindifferenceequations.springeropen.com/articles/10.1186/s13662-019-2321-z#rightslink
Keywords: Fuzzy shunting inhibitory cellular neural networks; Global exponential stability; Periodic solutions; Delay differential equations; Lyapunov functional; neural networks